Rural Development Programmes and Externalities : the report of the project funded by Planning Commission, Government of India, New Delhi - Selvarajan, E. Elango, R. (New Delhi Serials Publications, 2004)
With reference to Tamil Nadu, India.
Includes statistical tables.
Keywords: Rural development; Government policy -- India -Tamil Nadu -- Statistics